SAT0247 Social Role Participation in Patients with Ankylosing Spondylitis and Controls. (23rd January 2014) - van Genderen, S.; Plasqui, G.; Jacobs, P.; Heuft, L.; Luime, J.; Spoorenberg, A.; Arends, S.; Gignac, M.; Lacaille, D.; van der Heijde, D.; Landewe, R.; Boonen, A.
Abstract : Background: While it is well known that patients with ankylosing spondyltis (AS) experience restrictions in worker participation, information regarding participation in other social roles is lacking. Objectives: To assess and understand social role participation in patients with AS in comparison with a healthy control group using the social role participation questionnaire (SRPQ). Methods: In a cross-sectional study, subjects completed the SRPQ, which assesses the influence of health on the perceived importance of 11 diverse social roles (e.g., hobbies, traveling, relationships, employment) and one global participation question, as well as the satisfaction with the role performance. All items were rated on a 5 point likert scale ranging from 1= not important /not at all satisfied to 5= very important/very satisfied. From these scores the importance satsifaction gap was calculated (importance minus satisfaction with the role performance), indicating the discordance between role salience and role performance. Results: A total of 246 AS patients (mean age 51 ± 12 years; 62% males; mean disease duration of 17 ± 12 years) and 510 healthy controls (mean age 42 ± 15 years; 70% males) were included. The mean scores of importance and satisfaction with the role performance of the global participation question were 4.3 ± 0.8 and 3.0 ± 1.0, respectively for patients and 4.0 ± 0.9 and 3.6 ± 0.9, respectively for controls and were significantly different between groups for both measures P < 0.001. The difference of the importance-satisfaction gaps between patients and controls accros social roles varied between 0 and 1.1. Figure 1 illustrates the gaps for patients and controls for all social roles seperately. Image/graph: Conclusions: In comparison with a healthy population, patients with AS report larger importance-satisfaction gaps except for the social role of paid work. Future studies should explore the reasons for the difference in the gap between patients and controls as well as the contribution of the concept of the importance-satisfaction gap on the satisfaction with life. Disclosure of Interest: S. van Genderen: None Declared, G. Plasqui: None Declared, P. Jacobs: None Declared, L. Heuft: None Declared, J. Luime: None Declared, A. Spoorenberg: None Declared, S. Arends: None Declared, M. Gignac: None Declared, D. Lacaille: None Declared, D. van der Heijde: None Declared, R. Landewe: None Declared, A. Boonen Grant/research support from: MSD, Pfizer, Amgen, Abbott, Consultant for: Pfizer, Speakers bureau: Pfizer, UCB